2021
DOI: 10.3390/molecules26072047
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as Antibiotic Delivery Systems: A Promising Nanotechnological Strategy against Antimicrobial Resistance

Abstract: Antimicrobial drugs are key tools to prevent and treat bacterial infections. Despite the early success of antibiotics, the current treatment of bacterial infections faces serious challenges due to the emergence and spread of resistant bacteria. Moreover, the decline of research and private investment in new antibiotics further aggravates this antibiotic crisis era. Overcoming the complexity of antimicrobial resistance must go beyond the search of new classes of antibiotics and include the development of altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 115 publications
(181 reference statements)
0
62
0
Order By: Relevance
“…They also provide targeted delivery and controlled release of drugs. A positively charged liposome would target a negatively charged bacterial cell wall through electrostatic interactions [60,61]. The physicochemical properties would help in the accumulation of drugs at infected sites and direct interaction with bacteria [39].…”
Section: Discussionmentioning
confidence: 99%
“…They also provide targeted delivery and controlled release of drugs. A positively charged liposome would target a negatively charged bacterial cell wall through electrostatic interactions [60,61]. The physicochemical properties would help in the accumulation of drugs at infected sites and direct interaction with bacteria [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles including metallic nanoparticles, liposomes, and dendrimers appeared in response to the lack of antibiotics efficacy and drug resistance. These nanomaterials are very versatile, showing, for instance, the ability for encapsulation of antibiotics [ 114 , 115 ] and other antimicrobial agents. For example, it was recently demonstrated that the encapsulation of an antimicrobial glycolipid biosurfactant with the use of chitosan-based nanoparticles was effective against Helicobacter pylori biofilm [ 116 ].…”
Section: Antibacterial and Antibiofilm Strategiesmentioning
confidence: 99%
“…When the use of nanoparticles (NPs) as effective antimicrobial agents is considered, some key properties are also taken into account, such as their large surface area relative to a small size volume and their excellent predisposition for surface modifications. The development of nanotechnology for antimicrobial propose is widely investigated at the pre-clinical level, and some nanoparticles are already approved by the FDA for clinical use (as in the case of liposomal formulations and lipid-based vaccines) or are in clinical trials [ 114 ].…”
Section: Antibacterial and Antibiofilm Strategiesmentioning
confidence: 99%
“…A promising alternative to the search of new therapies are nanoantibiotics, the combination of approved antibiotics with the use of nanotechnology. Recent advances in this domain have enabled the development of drug delivery systems with improved pharmacokinetic characteristics and antimicrobial features [ 2 ].…”
Section: Introductionmentioning
confidence: 99%